2017
DOI: 10.1177/0886260517731311
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Economic Abuse and Mental Health Among Latina Intimate Partner Violence Survivors in the United States

Abstract: Currently, Latinos constitute the second largest and fastest growing minority group in the United States. Among this population, one in every six Latinas experience intimate partner violence (IPV) in her lifetime. Research has documented significant detrimental effects of physical, sexual, emotional, and psychological IPV on the physical, emotional, and cognitive well-being of various cultural/ethnic groups; however, few studies have focused on economic abuse, which may include tactics of economic control, eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 34 publications
3
40
0
1
Order By: Relevance
“…In the literature, it is stated that there are four different types of non-physical violence: emotional, psychological, social and economic violence [3]. Physical and sexual violence, however, refers to the type of violence related to physical intervention against women [2,4]. IPV is a comprehensive and multi-directional social problem associated with various health and social consequences.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, it is stated that there are four different types of non-physical violence: emotional, psychological, social and economic violence [3]. Physical and sexual violence, however, refers to the type of violence related to physical intervention against women [2,4]. IPV is a comprehensive and multi-directional social problem associated with various health and social consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Research is also beginning to document economic and work-related IPV among Latinas. For Latina survivors, physical and sexual IPVoften co-occurred with economic abuse (Davila et al 2017). Economic control, i.e., when the abuser controls or limits the victim's access to resources, was the most common form of economic abuse reported in this study.…”
Section: Prevalence Of Ipv Among Latinasmentioning
confidence: 74%
“…Economic control, i.e., when the abuser controls or limits the victim's access to resources, was the most common form of economic abuse reported in this study. Economic sabotage, such as when an abuser interferes with their partner's work outside the home, was also documented (Davila et al 2017;Stylianou et al 2013). In another study, Latinos who had used violence against their partners reported using several strategies to interfere with their partners' employment, such as on-the-job surveillance, on-the-job harassment, and work disruption tactics (Galvez et al 2011).…”
Section: Prevalence Of Ipv Among Latinasmentioning
confidence: 99%
See 2 more Smart Citations